Overview of Hand Injuries and Their Treatment at a Tertiary Care Hospital by Applying the Hand Injury Scoring System - Shrihari, Vivek (Medical Science: Trends and Innovations Vol. 3, 2025)
Background: Hand injuries form a substantial part of the workload of all accident and emergency departments and have a serious economic impact because they can significantly affect the ability to carry out useful employment. After forearm fractures, fractures in the hand are the second most common fracture, accounting for up to 20% of all fractures. Hand injuries are a major health problem all around the world; both in developing as well as developed countries. There are various causes of hand injuries which include occupational injuries, leisure activities, road traffic accidents, falls and other domestic injuries. The aim of the present study was to create a database of hand injury patterns in PIMS for assessing and scoring the severity of hand injury. Methods: This was a descriptive study that analyzed 442 hand injuries that were presented to the Department of Emergency Services and the outpatient departments of plastic and general surgery in the PIMS, Puducherry, India. The demographics of the hand injuries have been analyzed and studied. Scoring of the hand injuries has been done by the hand injury severity scoring system (HISS). Data were entered and analyzed using SPSS version 16. Descriptive statistics were recorded. Percentages and diagrammatic presentation of the findings of the study have been done. The management that was carried out for these patients has been documented and recorded. Results: A total of 442 patients were included in the study. Among them, 379 (85.75%) cases were male and 63 (14.25%) patients were female. Female subjects were more commonly affected in two age groups (1-15, 45-60). The distribution of the nature and etiology of injuries in both genders was similar, with occupational and crush injuries being the dominant mode of injury in both genders. 237 (53.6%) patients sustained injuries to their dominant hand, while 205 (46.4%) sustained injuries to their non-dominant hand. 31.09% of dominant hand injuries were found to be mild in severity. 28.43% of non-dominant hand injuries were found to be major in severity. There was an even distribution of injuries between severity scores among all the patients. The duration of hospital stay was increased with the severity of hand injury. 221 (50%) patients followed up for less than one month following their hand injuries whereas 69 (15.61%) cases were lost to follow-up. Among the followed-up patients, 126 (74.12%) subjects said they were normal at follow up and 44 (25.88%) said they had some residual impairment following their hand injuries. Of them, the daily activities of 33 patients were affected depending upon the severity of the injury. 409 (92.53%) patients required some form of surgical treatment, whereas 33 (7.47%) patients required only conservative treatment for their hand injuries. It is also noted that the psychological impact of a visible injury is significantly higher than non-visible disability. Plastic surgery has a huge role in reducing the patient’s psychological stress by correcting and improving the appearance of the injured hand wherever possible. Conclusions: HISS presented to be an important system for assigning the patients according to the score, in directing the patients to precise management and seems to be popular for excellent functional outcomes.